Production of Electricity from Renewable Energy Sources by Using the Example of a Municipality - Csizmadia, Ivett; Győri, Barnabás; Kulcsár, Balázs (International Journal of Engineering and Management Sciences, 2016)
In our paper we examine Komádi city’s renewable energy endowments. We touch upon the current manner which exploits the possibilities of the city and give suggestions to the municipal buildings in electricity demand could be ensured by means of renewable energy sources in what way